Pengaruh E-Service Quality terhadap Loyalty Intentions yang dimediasi oleh Variabel Perceivd Value pada Situs Belanja Online Zalora (Studi pada Konsumen di Kota Malang) - Safana Vida Nafisa Bakhri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The study aims at identifying the direct and indirect effect of E-Service Quality and Perceived Value on Zalora consumers’ Loyalty Intentions. This explanatory research attempts to elucidate the causal relations among variables through hypothesis testing. This study uses 100 respondents of Zalora consumers, selected using purposive sampling technique with the criteria of reaching 17 years of age at the minimum and having made at least one purchase in Zalora in the last 3 months. The research instrument was assessed using validity, reliability, and classical assumption test. The hypothesis was evaluated using t-test in SPSS 23, and the data are carefully examined using path analysis. The result of the study shows that e-service quality gives a significant direct effect on both loyalty intention of Zalora consumers and perceived value toward such online shopping website. Perceived value also significantly and directly influences loyalty intentions of Zalora consumers. This trend can lead perceived value to give a significant yet indirect effect in mediating the influence of e-service quality on loyalty intentions of Zalora consumers in Malang city.Keywords: E-Service Quality, Perceived Value, Loyalty Intentions